Extinction revisited: Alee effect and irreversibility in schooling fisheries - Coelho, M. P.; Filipe, J.A.; Ferreira, M. A. M.; Lopes, R. J. (International Journal of Latest Trends in Finance and Economics Sciences, 2013)
Important results of Colin Clark’s research in the 70s are used again in the discussion of the limits to the privatization of the fisheries. Those results highlighted the possibility of species extinction motivated by special forms of the natural growth function. This paper revisits the situation in which the growth function exhibits a non-feedback, or depensation, curve. The existence of non-shrinkage curves poses problems in determining the sustainable yield and has important implications for resource management. The so-called "Allee Effect" may explain the difficulties of recovery of certain stocks, even when there are a set of limitations to the fishing effort. Ultimately, it explains the extinction of some species: if we face a situation of non-critical feedback, an effect of irreversibility is introduced. These effects are considered in the schooling species fisheries case.